TRENDS IN HOSPITALIZATION FOR DIABETES MELLITUS AND SYSTEMIC ARTERIAL HYPERTENSION IN THE ELDERLY - Paula Cristina Gerhardt; Ana Carla Borghi; Carlos Alexandre Molena Fernandes; Thais Aidar de Freitas Mathias; Lígia Carreira (Universidade Federal do Paraná, 2016)
The present study aimed to assess trend in hospitalizationfor hypertension and diabetes among elderly individuals from the State of Paraná, in the 2001-2013 period. Ecological time-series study based on secondary data from the Information System of Brazil's Unified Health System (SUS) concerning the rates of hospitalization for hypertension and diabetes in the elderly, collected in April 2014and analyzed using descriptive statistics and polynomial regression.There were 59,481 hospitalizations for diabetes and 39,637for hypertension. The trend in hospitalization for diabetes was increasing among men (r2=0.85; p<0.001), at age groups 60-69 years and over 80 years (r2=0.66; p<0.042 and r2=0.69; p<0.002 respectively).Regarding hypertension, there was a decreasing trend for men and women (r2=0.91; p<0.001 andr2=0.82; p<0.001 respectively). The results were similar to those from other studies, stressing the need for information systems as a source for the planning of health actions targeted to elderly individuals.